Online Monitoring of Effluent Quality for Assessing the Effect of Wastewater Treatment Plant to Discharge into the Receiving Water: a review - Andri Taufick Rizaluddin; Henggar Hardiani (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2021)
In general, industries that use water in their production process will produce wastewater which usually contains a lot of polluting contaminants. It will affects the surrounding environment by contaminating the water bodies, which will adversely affect the health life of all living beings. Pollution that occurs in the some rivers in Indonesia has begun to raise concern for Indonesian Goverment. Some of the river locations already have heavy poluted status. The pollution is mostly caused by industrial waste and domestic waste along the river. Treatment plants for wastewater effluents are mandatory for any industry which discharges their wastewater effluents into the environment. Information on monitoring the quality of industrial wastewater is very important to be perceived by examining changes in water quality condition that are getting better or worse. It is necessary to develop a system that monitors the condition of industrial wastewater. Industrial wastewater monitoring is a device system that collects real time data. Online monitoring technology is one part that plays an important role in supporting activities to control marine environmental pollution. Real‐time monitoring of wastewater quality remains an unresolved problem to the wastewater treatment industry. One of the problem in most industries in Indonesia is that the operational and performance of wastewater treatment plants (WWTP) are still not optimal, and need to be improved. The application of industrial technology concept 4.0 and automation systems in the industry is expected to improve the WWTP supervision process which has advantages such as reducing down time, reducing consumption of raw materials, reducing the energy used, increasing productivity, improving product quality and making efficient use of resources and processes, so as to reduce industrial operating costs.